Precipitation Shortage in the High Ukrainian and Polish Carpathians - Kholiavchuk, Dariia; Cebulska, Marta (Air and Water – Components of the Environment” Conference Proceedings, Cluj-Napoca, Romania, 2021)
In the recent decades, droughts and dry episodes throughout a year have become common for both arid and humid regions. The Carpathian Mountains referred to as natural water towers are also the case. Accordingly, the study aims and distinguishing monthly and daily patterns and peculiarities of precipitation shortage in the high-mountain areas (above 1000 m) of the Polish and the Ukrainian Carpathians using monthly and daily data series (1984-2015) of weather stations Kasprowy Wierch (1991 m a.s.l), Dolina Pięciu Stawów (1670 m a.s.l) and Morskie Oko (1408 m a.s.l) in the Polish Carpathians, Play (1343 m a.s.l) and Pogegevskaya (1429 m a.s.l) in the Ukrainian Carpathians. Here, in all the months throughout a year, dry episodes have been detected. In the Polish Carpathians, represented by three measuring stations, the driest episodes in the years took place from August to October and January, and slightly less – about 11-16% in the remaining months. In the monthly context, the highest frequency of dry months, exceeding 20%, is detected in June both in Pogegevskaya, as well and in April and July in Play. In March, April, as well as November extreme atmospheric drought took place in the entire area of the Polish Tatra Mountains, the highest mountain range of the Polish Carpathians. In all the measuring stations of the area in November 2011, the precipitation amount did not exceed 11 mm. They accounted for less than 10% of the average multiannual precipitation sum. Alongside, the positive trend in the years from 1984 to 2015 with significance levels of 0.1 and 0.2 was only established in the lowest monthly precipitation sums at Pogegevskaya. The longest episodes without precipitation, periods that begin and end with a day without precipitation, are detected in most parts of the study area in October and November 2011, especially in the western and southern parts of the Polish Carpathians.
Keywords: atmospheric droughts, periods without precipitation, Standardized Precipitation Index, extremely dry periods, Carpathians